Potential Benefits of Plant-Derived Products on Broiler Meat Characteristics - A Short Review - Sugiharto Sugiharto (Universitas Bengkulu, 2022)
Herbal supplements have been researched for decades as a safe alternative to synthetic antioxidants. These natural supplements may help broilers enhance their meat quality, growth, and physiological circumstances. The phenolic compounds in herbal products can serve as antioxidants, thereby responsible for lessening the negative effect of stress before slaughter. One of the most critical factors impacting broiler meats' physical, chemical, and oxidative stability is stress before slaughter. Reducing stress levels during rearing may be anticipated to enhance broiler meat qualities. Some studies have found that herbal supplementation improves meat qualities, whereas others have no impact. The efficacy of herbal supplementation on meat characteristics may be determined by the nature and levels of herbal supplementation and the condition of the animals throughout the rearing. The use of plant-derived products in broiler production and their impact on carcass characteristics, physical and organoleptic qualities, chemical compositions, and oxidative stability of broiler meats are covered in this review.